An auction model of Canadian temporary immigration for the 21st century - Don J. DeVoretz (Institute for the Study of Labor (IZA), 2005)
Temporary Canadian immigration has grown beyond traditional programs for students, caregivers and agricultural workers to include trade-related temporary visas under NAFTA and the GATS. Several questions emerge under these temporary schemes including who should choose the number of temporary immigrants and under what employment conditions. This paper offers an alternative policy to the current government-determined quota on temporary visas to answer these two questions. Under the proposed scheme, offered in this paper a potentially-displaced Canadian worker places a job voucher up for auction on the Internet. If the Canadian worker finds an acceptable offer for his one-year (or less) voucher, then the temporary immigrant is admitted. Thus, under this auction scheme Canadian workers are compensated for the presence of temporary immigrants, and the actual number of temporary immigrants admitted depends on the total number of Canadian workers who sell their vouchers, not on a government fiat.
Keywords: F22; J61; 330; labour market; immigration; employment